2020
DOI: 10.1177/1535370219900185
|View full text |Cite
|
Sign up to set email alerts
|

The immune remodel: Weight loss-mediated inflammatory changes to obesity

Abstract: Obesity is an escalating world problem that contributes to the complexity and cost of treatment of metabolic disorders. Obesity is the result of increased storage of energy in the form of adipose tissue, reducing the quality of daily life, and interfering with longevity. Obesity is also a chronic, low-grade inflammatory disorder. The inflammatory processes affect many organ systems with expanded numbers of immune cells and increased cytokine production. Long-term weight loss is difficult to achieve and maintai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 184 publications
(242 reference statements)
0
21
1
1
Order By: Relevance
“…31 One of the important and most abundant immune cells infiltrating the adipose tissue in obesity are macrophages, 10 and MCP-1 is an important chemoattractant chemokine produced by adipose tissue mediating macrophage recruitment. 2 We found increased circulating levels of MCP-1 in obese individuals as compared to non-obese ones, but the difference was not statistically significant. Dahlman et al 32 found that expression of MCP-1 is significantly higher in obese as compared to lean individuals, but circulating levels showed no changes among their study groups suggesting that obesity produced only local changes of MCP-1 in adipose tissue.…”
Section: Discussioncontrasting
confidence: 57%
See 4 more Smart Citations
“…31 One of the important and most abundant immune cells infiltrating the adipose tissue in obesity are macrophages, 10 and MCP-1 is an important chemoattractant chemokine produced by adipose tissue mediating macrophage recruitment. 2 We found increased circulating levels of MCP-1 in obese individuals as compared to non-obese ones, but the difference was not statistically significant. Dahlman et al 32 found that expression of MCP-1 is significantly higher in obese as compared to lean individuals, but circulating levels showed no changes among their study groups suggesting that obesity produced only local changes of MCP-1 in adipose tissue.…”
Section: Discussioncontrasting
confidence: 57%
“…CRP is the most often measured inflammatory marker and has consistently correlated with weight, BMI and waist to hip ratios as well as insulin resistance. 2,20 CRP has become the marker of metainflammation. Based on the available literature and the findings of our study, obesity is associated with a general inflammatory response that cannot be simply attributed to mere imbalance between proand anti-inflammatory status.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations